Application review of dielectric electroactive polymers (DEAPs) and piezoelectric materials for vibration energy harvesting. (September 2016) - Yuan, Xuan; Changgeng, Shuai; Yan, Gao; Zhenghong, Zhao
Abstract: This paper reviews recent advances in vibration energy harvesting with particular emphasis on the solutions by using dielectric electroactive polymers (DEAPs) and piezoelectric materials. These smart materials are in essence capable of converting wasted vibration energy in the environment to usable electrical energy. Much previous researches have been devoted to studying the technology of harvesting mechanical energy using piezoelectric materials. The recent introduction of the DEAPs that exhibits large displacements under electric activation has led to their consideration as promising replacement for conventional piezoelectric materials. The properties of the two materials are described in this paper together with a comparison of their performance in relation with energy harvesting. Finally comparisons are made in the applications of vibration energy harvesting using these two materials. This paper has been written with reference to a large number of published papers listed in the reference section.